Resepsi Masyarakat Blitar Dalam Spiritual Transformation - Binti Nursita Putri (STAI Hidayatut Thullab Kediri, 2023)
Since the community of Blitar knew about study of spiritual transformation, the community has undergone a fundamental change in the terms of religious obedience. This problem is included into the study of phenomenologic spiritual transformation al Qur’an known as the living Qur’an. This study is expected to enlighten the phenomenon of spiritual transformation of in the community of Blitar used to face the social realities today. The method of this study was qualitative method using observation, interviews, and documentation as a research instrument. This study also used the phenomenological approach by Peter L. Berge and the theory of structural functionalism by Talcott Parsons. The research problems of this study are: first, how is the factual phenomenon of spiritual transformation. Second, how is the community’s reception to spiritual transformation. Third, how is the implication of spiritual transformation in social reality. The results of this study were: (1) each –citizen get a part as a householder of this activity, spiritual transformation. It is carried out once every months at PKH room. (2) the strengthening the relationship between transcendental and inner moods. (3) the means of making spiritual transformation strengthen the relationship of community in problem solving, strengthen interrelation in society, also strengthen a sense of empathy and affection.